GERAKAN KEBERSIHAN LINGKUNGAN MUSHOLA UNTUK MENYAMBUT DATANGNYA BULAN SUCI RAMADHAN DI DESA DAMARSI BUDURAN SIDOARJO - Muhamad RickyTirta Jagad Dhita (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Worship during the holy month of Ramadan requires clean and representative facilities to ensure the devotion and health of the congregation. This community service activity aims to improve the physical condition of the Damarsi village prayer room to make it a more hygienic and comfortable place of worship. The method used was Participatory Action Research (PAR), students actively participated directly with the community in a mutual cooperation action. The series of activities included a thorough cleaning of the interior area, starting from cleaning the ceiling, fan facilities, and window glass, to sterilizing the floor and arranging the imam's area and row dividers. In addition, the yard, water channels, as well as the ablution area and toilets were also cleaned to ensure all facilities were free of dirt and moss. The results of this activity showed a significant physical transformation of the prayer room, which has an impact on increasing the comfort of the congregation and strengthening social cohesion among residents. It was concluded that this active synergy succeeded in creating a conducive prayer space, with recommendations for the prayer room management